The northernmost record of King’s Tree Iguana, Liolaemus kingii (Bell, 1843) (Reptilia, Liolaemidae), in Chile - Jorge Mella; Jorge Mella-Romero; Felipe Reyes; Cristián Muñoz (Check List, 2020)
We report the presence of Liolaemus kingii (Bell, 1843) in Paso Río Frías, Villa La Tapera, Lago Verde, Aysén Region, Chile. The new record extends in 201 km the distribution range of this lizard and is the northernmost record to date in Chile. We highlight the importance of systematic fieldwork in Patagonian steppe to refine estimates of the number of reptile species in the Aysén Region.